(untitled) (Fiep Bulletin - online, 2017)
The present work refers to an internship report, in which will be treated on the resistance of the students of FinalElementary School, before the new contents in the classes of Physical Education. It sought to address methodological practicesof the Physical Education teacher and also to understand some reasons that causes this resistance. Based on the literaturereview, it was sought to understand the teacher-student relationship, the influence of the classes as a training practice and thehistorical-cultural rescue related to Physical Education and teacher. Therefore, he tried to emphasize some solutions to theresistance in class, and also suggestions for the teacher to help motivate the students, and thus avoid their withdrawal and lack ofcommitment in Physical Education classes.